2014
DOI: 10.1007/s10900-014-9916-9
|View full text |Cite
|
Sign up to set email alerts
|

Adapting the Andersen Model to a Francophone West African Immigrant Population: Hepatitis B Screening and Linkage to Care in New York City

Abstract: Hepatitis B virus (HBV) is highly endemic in West Africa and immigration from this region to the United States has greatly increased over the past quarter century. Using the Andersen Model as a conceptual framework, this study qualitatively examines francophone West African immigrants' perceptions of factors affecting access to HBV screening and linkage-to-care in New York City. Four focus groups were conducted with 39 purposefully selected participants. The focus groups were conducted in French, audio-recorde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(52 citation statements)
references
References 27 publications
2
42
2
Order By: Relevance
“…Overall, knowledge of viral hepatitis in the AI communities studied was quite minimal. Previous studies have shown that immigrant Asian and African communities have low levels of understanding of the causes and risk factors for liver cancer (28)(29)(30)(31)(32). In addition, our study indicates participants do not have an understanding of the different types of viral hepatitis, confirming a prior study assessing the knowledge of different viruses causing hepatitis (33).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…Overall, knowledge of viral hepatitis in the AI communities studied was quite minimal. Previous studies have shown that immigrant Asian and African communities have low levels of understanding of the causes and risk factors for liver cancer (28)(29)(30)(31)(32). In addition, our study indicates participants do not have an understanding of the different types of viral hepatitis, confirming a prior study assessing the knowledge of different viruses causing hepatitis (33).…”
Section: Discussionsupporting
confidence: 77%
“…Participants maintained cultural taboos associated with sharing positive viral hepatitis status and requested free communitywide screening HBV and HCV. In addition, a culturally-sensitive program will be required to minimize the burden of disease and to address the fear of exposure after diagnosis, thus, facilitating active screening, treatment, and prevention of viral hepatitis in AI (32,54).…”
Section: Resultsmentioning
confidence: 99%
“…[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and a further six articles provided a qualitative assessment of stigma, typically through either semi-structured interviews or focus group discussions. [35][36][37][38][39][40] The quantitative studies included a total of 15 studies conducted in people living with HBVor in the general population about people living with HBV and two studies that were conducted exclusively in healthcare providers. Seven of these studies assessed stigma exclusively in people living with HBV, 18,22,23,[27][28][29]31 two of which also conducted separate analyses in people without HBV, 23,31 and the remainder were conducted in general population samples.…”
Section: Literature Search Resultsmentioning
confidence: 99%
“…A total of six studies provided a qualitative assessment of patient or healthcare provider attitudes towards people living with HBV, including aspects of stigma and discrimination ( Table 2). [35][36][37][38][39][40] Two of the qualitative studies were conducted in people living with HBV in Malaysia and Iran. 36,37 In Malaysia, people frequently reported feeling anxious and/or distressed following initial diagnosis, which was attributed to a combination or lack of knowledge, stigma around HBV, and physicians' emphasizing HBV-related complications.…”
Section: Qualitative Studiesmentioning
confidence: 99%
“…Retention at 1 year was similar between patients with HBP and normal BP at baseline (86.8% vs. 80.9%; p  = 0.29). Increasing age (for each 10-year increase in age [1]: adjusted odds ratio [AOR] = 1.50; 95% confidence interval [CI] 1.20–1.93), male sex (AOR = 2.33, 95% CI 1.43–3.80), and overweight/obesity (AOR = 4.07; 95% CI 1.94–8.53) were associated with increased odds of HBP. Pre-ART CD4+ count was not associated with HBP (Table 1).…”
Section: Resultsmentioning
confidence: 99%